69.6k views
3 votes
If using the method of completing the square to solve the quadratic equation

x^2+ 15x - 23 = 0, which number would have to be added to "complete the
square"?

2 Answers

5 votes

Answer:


((15)/(2) )^2=(225)/(4)

Explanation:


x^2+15x-23=0\\x^2+15x+((15)/(2) )^2-((15)/(2))^2-23=0\\(x^2+15x+((15)/(2))^2)=23+((15)/(2))^2\\(x+(15)/(2))^2=(23*4+15^2)/4=317/4\\x+(15)/(2)=+(√(317))/(4)\\, -(√(317))/(4)\\\\x=-(15)/(2)-(√(317))/(4)\\\\, -(15)/(2)+(√(317))/(4)\\\\

User DJPB
by
4.7k points
3 votes

Explanation:

you would take half of 15 and then square it to get to number, which is 56.25

User Needoriginalname
by
4.5k points